Fig S4 - The influence of resource use on yield versus sale price trade-off in Australian vineyards - Bryce Boyd (21492412) (2025)
Residuals vs. fitted values plot for Model 2, illustrating the linearity and homoscedasticity of the residuals. (TIFF)